Motives for Using Tiktok among Communication Studies Students at Muhammadiyah University of Sidoarjo: Motif Penggunaan Tiktok di Kalangan Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Sidoarjo - Subagiyo, Nola Aisyah; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the motives for using the media of Communication Science students at Muhammadiyah University of Sidoarjo in using tiktok. This research is based on the fact that everyone who uses tiktok has its own motive, this motif has various uses, some use it because of the desire to seek knowledge, news information, entertainment information, and entertainment. This research method uses survey method with descriptive analysis type and quantitative approach. The sample of this study used 231 students who were actively using tiktok, which were taken through proportional random sampling. Data collection was carried out by distributing questionnaires via google form to Communication Studies students from 2018 to 2021 and analyzing the data using descriptive statistics. The results of the study showed that students of Communication Studies at Muhammadiyah University of Sidoarjo, students of the 2018 to 2021 class, used social media based on tiktok as much as 94% of entertainment motives and 93% of information motives. Because the two motives are included in the very good category and Communication Studies students at Muhammadiyah University of Sidoarjo tend to need more information and entertainment through social media tiktok which is considered to have a lot of educative, informative and entertaining content.